KONSEPSI SUJUD DALAM AL-QUR’AN: Analisis Komparatif Surah al-Baqarah: 34 dan al-Kahfi: 50 Perspektif Sayyid Quthb dan Imam al-Qurthubi - Shofa, Ida Kurnia (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2021)
This paper discusses the meaning of prostration in surah al-Baqarah: 34 and al-Kahf: 50 by Sayyid Quthb and Imam al-Qurtubi perspective. This study was conducted to analyze the meaning of prostration performed by angels to Adam. The substance of the prostration of angels to Adam gives rise to multiple interpretations, whether the prostration is meant the same as the prostration of a servant. Through a comparative analysis approach, the results of this study is Sayyid Quthb and Imam Al-Qurtubi understand the meaning of prostration in Surah Al-Baqarah: 34 and Surah Al-Kahf: 50 is to respect to the leader or as an exaltation. This is different from prostration in prayer performed by the servants of Allah to worship Him or called prostration of worship. Allah chose Adam as the leader and ordered the angels and devils to prostrate to him because Allah gave Adam more abilities that Allah did not give to other creatures